Monitoring sea surface salinity season variation from MODIS satellite data - Daqamseh, Saleh Taher Salem; Mansor, Shattri; Mahmud, Ahmad Rodzi; Pirasteh, Saied (IEEE, 2010)
This paper demonstrate the ability of MODIS data for mapping of seasonal salinity spatial distribution in Mersing and Semporna water. The objective of this work is to monitor the seasonal in-shore and open sea of sea surface salinity (SSS). The multi linear regression has been done for estimation salinity. In this study, the maximum amount salinity have been determined in the southwest Manson; which is 35.34 psu and the minimum value during north east Manson (31.60 psu). In conclusion, MODIS data can be used as a geomatica tool for accurately mapping of salinity surface along the Semporna of Sabah, with implementation of multi linear and minnet algorithms.